2014
DOI: 10.1007/s12272-014-0474-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-related inflammation and insulin resistance: a review of their intricate interdependency

Abstract: Chronic inflammation is a major risk factor underlying aging and the associated diseases of aging; of particular interest is insulin resistance during aging. Chronic inflammation impairs normal lipid accumulation, adipose tissue function, mitochondrial function, and causes endoplasmic reticulum (ER) stress, which lead to insulin resistance. However, some studies show that insulin resistance itself amplifies chronic inflammation. The activity of the insulin-dependent Akt signaling pathway is highlighted because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 67 publications
(75 reference statements)
2
69
0
1
Order By: Relevance
“…In contrast, USP10 deficiency aggravated HFD‐induced inflammation. The increased pro‐inflammatory cytokine levels inhibit insulin signaling and induce insulin resistance . After chronic HFD treatment, the activation of IRS1‐AKT activates PEPCK and G6Pase to promote gluconeogenesis and in turn facilitates hepatic lipogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, USP10 deficiency aggravated HFD‐induced inflammation. The increased pro‐inflammatory cytokine levels inhibit insulin signaling and induce insulin resistance . After chronic HFD treatment, the activation of IRS1‐AKT activates PEPCK and G6Pase to promote gluconeogenesis and in turn facilitates hepatic lipogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…The increased pro-inflammatory cytokine levels inhibit insulin signaling and induce insulin resistance. (21)(22)(23)(24) After chronic HFD treatment, the activation of IRS1-AKT activates PEPCK and G6Pase to promote gluconeogenesis and in turn facilitates hepatic lipogenesis. (25,26) Using liver-specific USP10 deficiency and overexpression mice, we demonstrated that USP10 could significantly ameliorate insulin sensitivity and glucose tolerance and enhance insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that isohumulones may reduce the activation of specific pattern recognition receptors on target tissues such as the gastrointestinal mucosal cells thereby reducing the triggering of the proinflammatory immune response which is associated with insulin resistance, dyslipidemia, and obesity [60,61].…”
Section: Influence Of the Hops-derived Isohumulones On Obesitymentioning
confidence: 93%
“…Over the past decade the interrelationship between the inflammatory and insulin signaling pathways has been elucidated [41]. In vitro assays with murine 3T3L1 adipocytes as well diabetic animal models indicated that the antiinflammatory effects of the isohumulones were associated with the improvement in insulin signaling [42,43].…”
Section: Effects Of Hops Isohumulones On Insulin Sensitivity and Metamentioning
confidence: 99%
“…Insulin resistance increases with aging, and is involved in several underlying mechanisms of sarcopenia induction. 5 Insulin is a catabolic hormone, which stimulates protein synthesis including that in muscle. Defects in insulin signaling can lead to reduced muscle synthesis.…”
Section: What Is Sarcopenia?mentioning
confidence: 99%